Potensi Keuangan Umkm Jasuke: Mendalami Hasil Penjualan di Kabupaten Bartim - Dicky Perwira Ompusunggu; Depi Tamara (Pusat Riset dan Inovasi Nasional, 2023)
This journal aims to analyze the results of UMKM operations in the Bartim area, which operates Padang Padang fresh snacks made from corn, milk and cheese or also called jasuke. Financial analysis is carried out based on sales results for the past year using several financial risks such as profitability risks, liquidity risk and activity risk, the data used in this study were obtained from UMKM jasuke's financial reports.